Species distribution modelling data for Phellinus ferrugineofuscus - Snäll, Tord; Mair, Louise (Swedish University of Agricultural Sciences, 2018)
These data consist of citizen science observations of Phellinus ferrugineofuscus in Sweden and the associated environmental variables at each data point. The data include a presence-absence dataset, a presence-only dataset, background data, and repeat visit data used in occupancy modelling. The data were applied in species distribution modelling using a variety of methods and full details of data compilation, sources and application can be found in Mair et al. (2017) Ecology and Evolution 7:368-378.

The data set consists of seven tab-delimited text files, in txt-format. The read_me file contains more information about the contents of the different files.

Data från observatiner av ullticka (Phellinus ferrugineofuscus) i Sverige.

För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/ecds0225

The data set consists of seven tab-delimited text files, in txt-format. The read_me file contains more information about the contents of the different files.
Species distribution modelling data for Phellinus ferrugineofuscus
Keywords: FOREST CONSERVATION; CONIFERS; FUNGI; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Biological Sciences; Biologi; Environment; Miljö